To clot or not to clot? Ad is the question—Insights on mechanisms related to vaccine‐induced thrombotic thrombocytopenia. (23rd August 2021) - Othman, Maha; Baker, Alexander T.; Gupalo, Elena; Elsebaie, Abdelrahman; Bliss, Carly M.; Rondina, Matthew T.; Lillicrap, David; Parker, Alan L.
Abstract: Vaccine‐induced immune thrombotic thrombocytopenia (VITT) has caused global concern. VITT is characterized by thrombosis and thrombocytopenia following COVID‐19 vaccinations with the AstraZeneca ChAdOx1 nCov‐19 and the Janssen Ad26.COV2.S vaccines. Patients present with thrombosis, severe thrombocytopenia developing 5–24 days following first dose of vaccine, with elevated D‐dimer, and PF4 antibodies, signifying platelet activation. As of June 1, 2021, more than 1.93 billion COVID‐19 vaccine doses had been administered worldwide. Currently, 467 VITT cases (0.000024%) have been reported across the UK, Europe, Canada, and Australia. Guidance on diagnosis and management of VITT has been reported but the pathogenic mechanism is yet to be fully elucidated. Here, we propose and discuss potential mechanisms in relation to adenovirus induction of VITT. We provide insights and clues into areas warranting investigation into the mechanistic basis of VITT, highlighting the unanswered questions. Further research is required to help solidify a pathogenic model for this condition.